2018
DOI: 10.1186/s13054-018-1990-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the High-flow Nasal Cannula for Adult Patients

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2018. Other selected articles can be found online at https://www.biomedcentral.com/collections/annualupdate2018. Further information about the Annual Update in Intensive Care and Emergency Medicine is available from http://www.springer.com/series/8901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 48 publications
3
101
0
7
Order By: Relevance
“…HFNC consists of humidified, high flow (up to 60 L/min) oxygen with a maximum FiO 2 of 100%. At high flow rates, HFNC is generally considered to provide 4-6 cm H 2 O of added inspiratory pressure 119. Prospective RCTs in both the ICU and the postoperative period have found that HFNC is non-inferior to NIPPV in terms of preventing respiratory failure but is better tolerated in terms of patients’ comfort 120121.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…HFNC consists of humidified, high flow (up to 60 L/min) oxygen with a maximum FiO 2 of 100%. At high flow rates, HFNC is generally considered to provide 4-6 cm H 2 O of added inspiratory pressure 119. Prospective RCTs in both the ICU and the postoperative period have found that HFNC is non-inferior to NIPPV in terms of preventing respiratory failure but is better tolerated in terms of patients’ comfort 120121.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…, Hernández et al . , Helviz & Einav ) and (5) decreased ventilatory drive and breathing effort in obstructive disease (Di Mussi et al . ), allowing the use of HOT in hypoxaemic and hypercapnic respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, a non-invasive oxygen delivery technique known as high-flow oxygen therapy (HOT) has emerged as an alternative to conventional oxygen therapy (Helviz & Einav 2018). This system allows for delivery of warmed and fully humidified gas with high flow rates of up to 60 L/minute through a specific high-flow nasal cannula, with a FIO 2 ranging from 21 to 100% (Frat et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HHFNC has been recommended for spontaneously breathing adults with hypoxemia, or discomfort from increased respiratory effort . It has been used in adults with acute respiratory failure, pneumonia, immunocompromise, during airway procedures, post‐extubation and palliative care . The utility of HHFNC in hypercapnic respiratory failure is still uncertain .…”
Section: What Are the Indications For Hhfnc?mentioning
confidence: 99%
“…5,[8][9][10][11] It has been used in adults with acute respiratory failure, 12 pneumonia, 12 immunocompromise, 13 during airway procedures, 14 post-extubation 15 and palliative care. 3,16 The utility of HHFNC in hypercapnic respiratory failure is still uncertain. 7,17 It is seen as a useful alternative in a patient who does not tolerate NIV.…”
Section: What Are the Indications For Hhfnc?mentioning
confidence: 99%